2014
DOI: 10.1088/1742-6596/529/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Strong-disorder magnetic quantum phase transitions: Status and new developments

Abstract: This article reviews the unconventional effects of random disorder on magnetic quantum phase transitions, focusing on a number of new experimental and theoretical developments during the last three years. On the theory side, we address smeared quantum phase transitions tuned by changing the chemical composition, for example in alloys of the type A1−xBx. We also discuss how the interplay of order parameter conservation and overdamped dynamics leads to enhanced quantum Griffiths singularities in disordered metal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
(69 reference statements)
0
4
0
1
Order By: Relevance
“…In solid solutions of the type Ba1-xSrxRuO3, when increasing the values of x, the nine-layer structure with stacking sequence (chh)3 (9R) transforms to the four-layer structure (ch)2 (4H) and finally to the classical perovskite type structure (c)3 (3C) at x is about 1/6 and 1/3, respectively 33 . The 4H and 9R forms of BaRuO3 have substantially different electronic properties 35 , and even the Sr1-xCaxRuO3 perovskites in the more familiar cubic perovskite structure types are famously enigmatic quantum materials [36][37][38] . In the event that readers are not familiar with magnetism we point out that the A ions in perovskites, with the exceptions of the rare earths, are not magnetic (i.e.…”
Section: Mixtures Of Cubic Plus Hexagonal Packingmentioning
confidence: 99%
“…In solid solutions of the type Ba1-xSrxRuO3, when increasing the values of x, the nine-layer structure with stacking sequence (chh)3 (9R) transforms to the four-layer structure (ch)2 (4H) and finally to the classical perovskite type structure (c)3 (3C) at x is about 1/6 and 1/3, respectively 33 . The 4H and 9R forms of BaRuO3 have substantially different electronic properties 35 , and even the Sr1-xCaxRuO3 perovskites in the more familiar cubic perovskite structure types are famously enigmatic quantum materials [36][37][38] . In the event that readers are not familiar with magnetism we point out that the A ions in perovskites, with the exceptions of the rare earths, are not magnetic (i.e.…”
Section: Mixtures Of Cubic Plus Hexagonal Packingmentioning
confidence: 99%
“…Parts of this topic have been reviewed recently in Refs. (18,19,78,79). We therefore only summarize the key concepts and emphasize the refined classification developed in Ref.…”
Section: Disordered Phase Transitionsmentioning
confidence: 99%
“…Several other examples of magnetic quantum Griffiths phases in metallic systems have been found in recent years (see Refs. (19,79) and references therein). In 2015, Xing et al (133) reported Griffiths singularities near the superconductor-metal transition in Ga thin films.…”
Section: (A) (B)mentioning
confidence: 99%
“…The effects of disorder and/or impurities have been considered as well, unveiling quite a rich phenomenology that ranges from the so-called Griffiths-McCoy singularities [49] to the rounding of a quantum phase transition [50] (for an up-to-date review of theoretical and experimental aspects, see Ref. [51]). …”
Section: Introductionmentioning
confidence: 99%